1987
DOI: 10.1017/s0043174500026916
|View full text |Cite
|
Sign up to set email alerts
|

Red Rice (Oryza sativa) Control with Herbicide Treatments in Soybeans (Glycine max)

Abstract: Preplant incorporation of alachlor [2-chloro-N-(2,6-diethylphenyl)-N-(methoxymethyl)acetamide] at 3.6 kg ai/ha, metolachlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-1-methylethyl)acetamide] at 2.2 kg ai/ha, and tank mixtures of imazaquin {2-[4,5-dihydro-4-methyl-4-(1-methylethyl)-5-oxo-1H-imidazol-2-yl]-3-quinolinecarboxylic acid} with either alachlor at 0.14 + 2.2 kg ai/ha or metolachlor at 0.14 + 1.1 kg ai/ha controlled >90% red rice (Oryza sativaL. # ORYSA) in soybeans [Glycine max(L.) Merr.]. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 5 publications
3
29
0
Order By: Relevance
“…These are soil-applied residual herbicides that are absorbed primarily by shoots and secondarily through roots of germinating seedlings, where disrupted cell division results in distorted tissue formation or plant death (Fuerst 1987). Experiments by Khodayari et al (1987) in soybean production demonstrated effective weedy rice control by VLCFA-inhibiting herbicides. When applied PPI, S-metolachlor at 2.2 kg ai ha −1 or alachlor at 3.6 kg ha −1 provided greater than 90% control of weedy rice in soybean production (Khodayari et al 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are soil-applied residual herbicides that are absorbed primarily by shoots and secondarily through roots of germinating seedlings, where disrupted cell division results in distorted tissue formation or plant death (Fuerst 1987). Experiments by Khodayari et al (1987) in soybean production demonstrated effective weedy rice control by VLCFA-inhibiting herbicides. When applied PPI, S-metolachlor at 2.2 kg ai ha −1 or alachlor at 3.6 kg ha −1 provided greater than 90% control of weedy rice in soybean production (Khodayari et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments by Khodayari et al (1987) in soybean production demonstrated effective weedy rice control by VLCFA-inhibiting herbicides. When applied PPI, S-metolachlor at 2.2 kg ai ha −1 or alachlor at 3.6 kg ha −1 provided greater than 90% control of weedy rice in soybean production (Khodayari et al 1987). Zemolin et al (2014) evaluated weedy rice control in soybean using PRE and early POST applications of S-metolachlor at 768, 1,152, and 1,680 g ha −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Red rice is often cited as one of the 10 most troublesome weeds in cultivated rice fields in the southern United States (Avila et al 2005; Craigmiles 1978; Khodayari et al 1987; Webster 2000). Barnyardgrass is another troublesome rice weed that can reduce rice yield by as much as 80% (Smith 1965).…”
Section: Introductionmentioning
confidence: 99%
“…In a conventional soybean program, the effectiveness of preplant incorporated (PPI), preemergence (PRE), and postemergence (POST) herbicides are dependent on adequate soil moisture. Alachlor PPI controlled red rice at least 95%, but imazaquin plus metolachlor applied PRE with inadequate soil moisture controlled red rice 68% (Khodayari et al 1987). Imazethapyr applied at 70 g ai/ha controlled red rice at the five-leaf stage at least 90% (Askew et al 1998), but because of potential carryover the next year, it could be detrimental to conventional rice varieties (Johnson et al 1993).…”
Section: Introductionmentioning
confidence: 99%